Sistem Pakar Untuk Pemilihan Rujukan Online Pada Klinik Murni Kantor Cabang Pematang Siantar Menerapkan Metode Forward Chaining - Sari, Dwi Ratna; Gunawan, Indra; Nasution, Zulaini Masruro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The National Health Insurance is implemented with a tiered referral system starting from the FKTP. The high number of referrals at the Pure Clinic which was developed means that the implementation of the online referral system has not been going well. The purpose of the study was to see the adjustment of the implementation of the online referral system in the JKN era at Pure Clinic based on existing laws and policies. This research is a descriptive observational research, and design. This study triangulated to obtain in-depth information on the intervention of data reference reference documents, recording books, records, and referral letters, interviews with referrals, and observations without giving